Implementation of Green Human Resource Management in Improving Environmental Performance at Hospital in Makassar - Ab, Fitrawati; Wahyuni, Dewi Urip (Innovation Business Management and Accounting Journal, 2023)
Environmental performance is one of the factors in the Environmental Quality Index. Most of the previous research on environmental performance and GHRM was conducted in the analysis unit of the manufacturing industry, while other industrial fields have not been studied much including hospitals. In fact, the hospital is one of the fields of business that is quite related to the environment. This lesson aims to analyze the effect of GHRM which consists of Green Recruitment and Selection, Green Training, and Green Compensation variables partially or together on the environmental performance of hospitals in Makassar City. The Grand Theory used in this research is Ecocentrism Theory and Triple Bottom Line. The population in this study were hospital employees at government hospitals in Makassar City, amounting to 2,270 people. By using the Slovin formula and the stratified proportional random sampling method, the number of samples that became respondents in this study was 248 people. This research is processed with multiple linear regression analysis techniques. The results show that Green Recruitment and Selection, Green Training, and Green Compensation partially have a significant effect on environmental performance in hospitals in Makassar City. The results also show that Green Recruitment and Selection, Green Training, and Green Compensation together also have a significant effect on environmental performance.